2017
DOI: 10.1128/msphere.00054-17
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii AP2IX-4 Regulates Gene Expression during Bradyzoite Development

Abstract: Toxoplasma gondii is a single-celled parasite that persists in its host as a transmissible tissue cyst. How the parasite converts from its replicative form to the bradyzoites housed in tissue cysts is not well understood, but the process clearly involves changes in gene expression. Here we report that parasites lacking a cell cycle-regulated transcription factor called AP2IX-4 display reduced frequencies of tissue cyst formation in culture and in a mouse model of infection. Parasites missing AP2IX-4 lose the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 51 publications
6
63
0
Order By: Relevance
“…A single family of DNA-binding proteins, the ApiAP2s, has been investigated for their role as Toxoplasma transcription factors and mediators of differentiation. While the phenotypes associated with many ApiAP2 mutants are striking, no single gene knockout has resulted in a complete block of differentiation, leading to the assumption that multiple transcription factors regulate Toxoplasma bradyzoite development Huang et al, 2017;Jeffers et al, 2018;Radke et al, 2013;Walker et al, 2013). By screening a wider range of putative nucleic-acid binding proteins, especially those containing well-conserved DNA-binding motifs such as zinc finger and Myb-like domains, we discovered that inactivation of BFD1 completely ablates bradyzoite formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A single family of DNA-binding proteins, the ApiAP2s, has been investigated for their role as Toxoplasma transcription factors and mediators of differentiation. While the phenotypes associated with many ApiAP2 mutants are striking, no single gene knockout has resulted in a complete block of differentiation, leading to the assumption that multiple transcription factors regulate Toxoplasma bradyzoite development Huang et al, 2017;Jeffers et al, 2018;Radke et al, 2013;Walker et al, 2013). By screening a wider range of putative nucleic-acid binding proteins, especially those containing well-conserved DNA-binding motifs such as zinc finger and Myb-like domains, we discovered that inactivation of BFD1 completely ablates bradyzoite formation.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will need to address the function of BFD1 during acute and chronic mouse infection. Mutations resulting in decreased rates of differentiation in cell culture generally display more profound defects in mice; however, the specificity of the ∆BFD1 phenotype will help define the role of bradyzoites in pathogenesis and immunological memory during Toxoplasma infection (Al-Anouti et al, 2004;Huang et al, 2017;Jeffers et al, 2018;Saeij et al, 2008). ∆BFD1 parasites may also represent an ideal attenuated vaccine strain, capable of proliferating robustly yet unable to enter a chronic state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of AP2 proteins in gene regulation has also been investigated to a lesser degree in T. gondii , where several AP2 proteins have been implicated in regulating progression through the cell cycle 14 as well as crucial virulence factors 15 . Other studies have implicated AP2s in regulating a developmental transition 16 . Radke et al 17 recently characterized a T. gondii AP2 and showed that this molecule acts as a repressor of bradyzoite development.…”
Section: Discussionmentioning
confidence: 99%
“…In Plasmodium , AP2 factors have been shown to regulate stage-specific gene expression required for life cycle stage differentiation [6369]. Similarly, in Toxoplasma , a complex interplay of transcriptional activators and repressors are involved in coordinating bradyzoite conversion [7073]. Epigenetic changes such as histone modifications also contribute to the activation and repression of stage-specific genes during latency [55,67].…”
Section: Eif2 Is the Gatekeeper Of The Isr And Latencymentioning
confidence: 99%